A efetividade da oxigenoterapia hiperbárica na cicatrização de lesões vasculares crônicas de membros inferiores em adultos: revisão sistemática com metanálise em rede - Rorato, Alexsandra Micheline Real Saul (2021)
Hyperbaric oxygen therapy is a therapeutic modality in which the patient breathes pure oxygen (100%), while under pressure 2 to 3 times the atmospheric pressure at sea level, inside a hyperbaric chamber. HBO is indicated as an adjuvant treatment to acute and chronic skin lesions. However, the profile of efficacy and safety of the HBO remains controversial, due to small sample randomized clinical trials and the geographical location of these studies with small samples, and the lack of information of some professionals. The objective of the research was to assess the effectiveness of hyperbaric oxygen therapy on lower limb chronic vascular lesions in adults. The method followed the trajectory of a systematic review (SR) of literature, in accord with the methodological procedures of Joana Briggs Institute (JBI), to standardize and ensure credibility of the evidence and also meta-analyses in a network using the software CINeMA as data synthesis method, aiming to increase the study strength. To make the SR, was used the mnemonic PICO composed of Population (patients with age equal or above 18 years with lower limb chronic vascular lesions), intervention (use of HBO), comparison (laser therapy, dressing, placebo), and outcome (healing). As a result of the research, the included studies were composed of 14 ECR, one quasi-experimental, and three cohort studies. The treatment based on using the hyperbaric oxygen therapy, associated to the dressing, reduces the risk of amputations when compared to the dressing alone (RR 0,167; IC95%: 0,057 – 0,485), to placebo (RR 0,174; IC95% 0,048 – 0,636) and hyperbaric oxygen therapy (RR 0,171; IC95% 0,052 – 0,560). Amongst other treatments, no significant difference was verified. Conclusion: HBO did not show a difference from the other interventions on matters of healing and wound reduction. HBO is not effective compared to the other treatments. However, on what matters amputation, the HBO was effective, reducing the risk of amputation when compared to other treatments and should be recommended to clinical practice starting from this meta-analysis in network.